IMPLEMENTASI SISTEM PENCEGAH KESALAHAN PEMBERIAN OBAT HIPERTENSI SEBAGAI BAGIAN DARI LAYANAN E-HEALTH - Reni Soelistijorini; Mike Yuliana; Lina Pratiwi (SENTIA 2016, 2016)
Errors medicine delivery in the treatment process can be dangerous for patients who can cause adverse drug reactions. This can occur because of allergies, medicine-medicine interactions, medicine interactions with diseases and medicine incompatibility which include duration of therapy, dose, route of administration, and amount of medicine. Hence it takes knowledge and thoroughness physicians in selecting drugs for patients. In this research will be made medication error prevention systems for hypertension that is integrated with the Hospital Information System (HIS) which is a web-based electronic prescribing application by using fuzzy to provide medicine’s recommendations to physicians (e-prescribing). Experiment results for several variations of the criteria show that the amount of medicine’s recommendation by using OR operator is more than AND operator. When using AND operator, fire strenght values obtained by functions mininimum thus taking the lowest value of the selected set degrees of membership. The value of fire strenght that full fill recommendation should be more than 0 and maximum value is 1. Contrary with OR operator, the value of fire strenght obtained by max function where the degree of membership that taken is the greatest.